Hubungan Konsumsi Jajanan Dan Perilaku Gizi Seimbang Dengan Status Gizi Remaja Di SMK Muhammadiyah 3 Palembang - Heri Shatriadi; Soleha, Siti (jurnal kesehatan terapan sains dan teknologi, 2024)
Background: Nutritional status is a measure of success in meeting nutritional needs for children and the use of nutritional substances which is announced by the child's weight and height. The nutritional needs for teenagers are very large because they are still growing. Teenagers need energy/calories, protein, calcium, iron, zinc and vitamins to fulfill physical activities such as activities at school and daily activities. Every teenager wants a healthy body condition so they can fulfill physical activities. Consuming energy that comes from food, the energy obtained will cover the energy intake that has been expended by a person's body. The nutritional status of adolescents is influenced by eating behavior where adolescents prefer to eat sweet and fast food which results in overweight problems. The Purpose : This research aims to determine the relationship between snack consumption and behavior regarding balanced nutrition with the nutritional status of teenagers at SMK Muhammadiyah 3 Palembang. Methods : This research is an observational study with a cross-sectional approach. The population in this study were students of SMK Muhammadiyah 3 Palembang, totaling 270 students and sampling was carried out using a simple random sampling method, namely 161 people. Results : The results of the statistical analysis showed that 92.5% of snack consumption among teenagers was categorized as low, 85.5% of the behavior regarding balanced nutrition among teenagers was mostly categorized as not good, 84.5% of the nutritional status of teenagers was mostly categorized as good nutrition, with a p-value value 0.018 < 0.05. Conclusion : There is a significant relationship between snack consumption and the nutritional status of teenagers at SMK Muhammadiyah 3 Palembang as evidenced by a ρ-value of 0.018 < 0.05.